VD_FINDINFO Jug / 2024 / 549 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
EMPLOYÉ PUBLIC, RÉSILIATION IMMÉDIATE, DÉLAI DE RÉSILIATION, JUSTE MOTIF, RELATION DE CONFIANCE, ENSEIGNANT, LIBERTÉ D'EXPRESSION | 337 CO, 337c CO, 16 Cst., 50 LPers-VD, 61 LPers-VD, 124 RLPers-VD